A new class of E-optimal regular graph designs - Ghosh D.K.; Thannippara, Alex; Joseph O.C. (Utilitas Mathematica, 2008)
Mitchell and John (1976) defined and constructed regular graph (RG) designs for equi-replicated and proper block designs. However, he didn't discuss RG designs with unequal block sizes. Hence in this investigation, we have studied the construction and optimality of RG designs with unequal block sizes. Moreover, in this investigation we have established that a class of two associate partially efficiency balanced design is, in fact RG designs. We, also obtained RG designs by adding two RG designs having the same treatments and same block size. Further, we have shown that the existence of a BIB design with λ = 2 implies the existence of an RG design, by deleting a particular treatment and those blocks in which that particular treatment is present.